Is early mobilisation better than immobilisation in the treatment of wrist sprains?. Issue 3 (3rd May 2016) - Clementson, Martin; Thomsen, Niels; Jørgsholm, Peter; Besjakov, Jack; Björkman, Anders
Abstract: Objective : Posttraumatic radial sided wrist pain is common and can represent a fracture or a ligament injury. However, in some patients radiographs and MRI are normal, indicating no specific diagnosis other than a wrist sprain. There is no consensus on the ideal treatment for this patient group. The aim was to investigate if patients with posttraumatic radial sided wrist pain and MRI not showing signs of fracture or SL-ligament injury should be treated with immediate mobilisation or 2 weeks cast immobilisation. Method : Forty-three patients, aged 18–64 years, were randomised to either a dorsal wrist cast for 2 weeks ( n  = 21), or immediate mobilisation ( n  = 22). Follow-up at 2, 4, and 6 weeks included clinical examination, self-assessment questionnaires (DASH, VAS), and recording of days on sick-leave. Results : At 2 weeks patients treated in a cast had reduced wrist range of motion, ROM (77% vs 96%, p  =   0.011), and higher DASH score (median 37 vs 18, p  =   0.009) compared to patients treated with immediate mobilisation. At 4 weeks, DASH score was still higher in the group treated in a cast (median 14 vs 4, p  =   0.01), but there was no difference in ROM. At 6 weeks there were no differences in any outcome measure between the groups. Furthermore, there was no significant difference in sick-leave between the groups (median 27 days vs 14 days, p  =   0.077). Conclusion : Patients with radial sided wrist pain where MRI does not demonstrate fracture or SL ligament injury do not benefit from cast immobilisation and can be treated with early mobilisation.